Uma contribuição ao estudo da estimativa do potencial hidrelétrico de pequenas centrais hidráulicas - Ferreira, Jacson Hudson Inácio (2014)
The aim of this masterthesis is to study and develop a methodology for the first stage of the deployment of a Small Hydraulic Plant (SHP), the Estimate Hydroelectric Potential, stage in which is studied the favorable and unfavorable situations to the deployment of small plants. Basing on environmental, technical and economic criteria of a watershed, according secondary data that are provided by agencies and institutions responsible for each criterion. Data collections for the study observe the geological and geotechnical, environmental, infrastructure and logistics, water availability and topography aspects. Moreover, it presents the use of GIS (Geographic Information Systems) to generate maps where relevant aspects are presented and analyzed, and it use the Hydrology Statistics for the hydrological study, to verify the flow of a river or precipitation at a local or region. At the end, it presents the estimate average energy generated, or average power, basing first on the variation of flow over an average year, and constant height, then with constant values of flow and height, estimating the specific power location, the type of water turbine, power and voltage of electric generator. It was applied a study case of the methodology in the watershed of the Tijuco river, limited to the city of Ituiutaba MG.